Novel Cu–Mg–Ni–Zn–Mn oxide thin film electrodes for NIR photodetector applications. Issue 14 (31st March 2021) - Wang, Tzu-Hsuan; Kuo, Chia-Tung; Chung, Pin-Hung; Liu, Chao-I; Lu, You-Yan; Lee, Yi-Ting; Yew, Tri-Rung
Abstract : CMNZM thin films generate electron–hole pairs under NIR light illumination and separate under an applied electric field. Abstract : This study reports the optical and photoconductive characteristics of the Cu–Mg–Ni–Zn–Mn oxide thin films with and without post-annealing in air. The Cu–Mg–Ni–Zn–Mn oxide thin films reveal a narrow bandgap of 1.96 eV and demonstrate the characteristics of an n-type semiconductor. The thin films exhibit a spinel crystal structure characterized by X-ray diffractometer and transmission electron microscopy. The p + -Si-substrate/Cu–Mg–Ni–Zn–Mn-oxide/indium-tin-oxide sandwich-structure devices were fabricated for the photoconductive characteristic investigation of Cu–Mg–Ni–Zn–Mn oxide thin films deposited by radio-frequency (RF) sputtering. The devices showed a high external quantum efficiency (EQE) of 96% under 800 nm wavelength illumination at a bias of −2 V. A fast response rise-time of 13 ms and a fall-time of 11 ms were also obtained. Hence, the Cu–Mg–Ni–Zn–Mn oxide thin films pave the way for developing high efficiency Schottky barrier photodetectors.